Investigation on Lost Circulation Materials (LCM) Derived From Durian Peel Waste For Drilling Fluid Formulation - Raieza Hanim Rahiman, Raieza Hanim (Universiti Teknologi Petronas, 2008)
This report concerns on investigation on lost circulation materials (LCM) derived from durian peel waste for drilling fluid formulation. The project mainly aims to study the effectiveness of using durian peel as LCM additives to prevent the lost circulation problem.